2006
DOI: 10.1002/j.2161-0045.2006.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated Work‐Family Conflict: Effects of Gender, Self‐Efficacy, and Family Background

Abstract: Anticipated levels of 2 types of work-family conflict (WFC) were studied among 358 students from 2 universities. The study examined the contribution of gender, parental models of child care and housework, and self-efficacy to the variance in anticipated WFC. Findings demonstrated that the bidirectionality of the relations between work and family life also exists in anticipated conflicts. A number of gender-related differences emerged: Women anticipated higher levels of work interfering with family and family i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
196
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(218 citation statements)
references
References 35 publications
14
196
0
8
Order By: Relevance
“…Anticipated work-family conflict was a unidimensional scale indicating that South African students do not distinguish between the family to the work and work to family directionality of AWFC (c.f., Cinamon, 2006;Gutek et al, 1991), which is consistent with many other applications of AWFC (Weer et al, 2006;O'Shea & Kirrane, 2008;Bu & McKeen, 2000;Livingston Burley & Springer., 1996). Similarly, self-efficacy to manage future work-family conflict (SE-FWFC) was a unidimensional scale (Hennessy 7 Lent, 2008).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Anticipated work-family conflict was a unidimensional scale indicating that South African students do not distinguish between the family to the work and work to family directionality of AWFC (c.f., Cinamon, 2006;Gutek et al, 1991), which is consistent with many other applications of AWFC (Weer et al, 2006;O'Shea & Kirrane, 2008;Bu & McKeen, 2000;Livingston Burley & Springer., 1996). Similarly, self-efficacy to manage future work-family conflict (SE-FWFC) was a unidimensional scale (Hennessy 7 Lent, 2008).…”
Section: Resultssupporting
confidence: 87%
“…ANOVA showed no significant main effect for gender, which means that males and female students do not differ in terms of their AWFC; though there is a difference depending on whether the student's mother worked full-time or not. Both Cinamon (2006) and Livingston et al (1996) found that females had significantly higher levels of AWFC than male students did; they did not consider whether students' mothers had worked full-time during the students' childhood. There was no significant difference between black and white students on AWFC.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Los Estados Unidos lideraron la producción académica sobre el tema con más de 30 % de los estudios, siendo Israel el segundo país más productivo. Sobre los autores o grupos de autores que más presentan estudios en esta revisión, las mayores frecuencias fueron de Hugo Ferrari Cardoso, MakiliM NuNes Baptista, FaBiáN Javier MaríN rueda Rachel Gali Cinamon (Cinamon, 2006;, investigadora de la Universidad de Tel Aviv, en Israel, y Deirdre O´Sullivan, David R. Strauser y Alex W. K. Wong, investigadores de la Universidad de Illinois, en los Estados Unidos (Strauser, O´Sullivan, & Wong, 2010;O´Sullivan, Strauser, & Wong, 2012).…”
Section: Discussionunclassified
“…En relación con esos estudios e investigadores, Cinamon en sus dos trabajos investigó la relación entre la percepción de autoeficacia con las demandas del contexto profesional y familiar en una muestra de trabajadores, o sea, investigó las temáticas conflictos de papeles (trabajo y familia) y la percepción de creencias de autoeficacia para resolver conflictos en ambas situaciones (Cinamon, 2006;. Por su parte, Deirdre O´Sullivan, David R. Strauser y Alex W. K. Wong en los dos estudios tuvieron como interés estudiar la relación entre aspectos de la personalidad y la percepción de creencias de autoeficacia en el trabajo en muestras de personas con deficiencia y que fueron rehabilitadas profesionalmente (Strauser, O´Sullivan, & Wong, 2010;O´Sullivan, Strauser, & Wong, 2012).…”
Section: Discussionunclassified